Perceived stress and dietary choices: The moderating role of stress management. (August 2016) - Errisuriz, Vanessa L.; Pasch, Keryn E.; Perry, Cheryl L.
Abstract: Many college students exhibit unhealthy eating behaviors, consuming large quantities of high-fat foods and few fruits and vegetables. Perceived stress has been linked to daily dietary choices among college students; however, this work has been conducted among predominantly white, female populations. The role of perceived stress management in moderating this relationship is unclear. This study investigated the relationship between perceived stress and dietary choices among a diverse sample of male and female college freshmen and assessed whether perceived ability to manage stress moderated this relationship. 613 students from a large, public university completed an online survey which assessed past week consumption of various foods and beverages (e.g. soda, fast food, fruits, vegetables), as well as perceived stress and ability to manage stress. Hierarchical linear regression examined the association between perceived stress and past week dietary choices, and the moderating effect of perceived ability to manage stress, controlling for demographic variables. Perceived stress was positively associated with past week soda, coffee, energy drink, salty snack, frozen food, and fast food consumption ( p < 0.05). Perceived stress management moderated the relationship between stress and sweet snack consumption. Individuals who reported low ability to manage stress consumed greater amounts. Findings indicate greater stress is associated with poor dietary choices among college freshmen. The relationship between stress and sweet snack consumption was exacerbated among those who reported low ability to manage stress. It may be important for college nutrition education programs to focus on the relationship between stress and diet and promote effective stress management techniques. Highlights: We assessed the association between perceived stress and diet in college freshmen. Perceived stress was positively associated with unhealthy food and beverage intake. Stress management moderated relationship between stress and sweet snack intake.